The Analysis of the Relationship between Personality Characteristics and Auricular Anatomy - Rengin Kosif; Murat Diramali; Selin Yilmaz (Journal of Interdisciplinary Sciences)
The anatomy of the auricle has guided us in plastic surgery, genetics, and forensics. Concrete scientific study about personality analyze with the anatomy of the auricle has not been conducted. In this study, it was scientifically researched whether anatomy of auricle can give us clues on personality characteristics or not. The photographs of students were taken via a digital camera and a 45 item personality test was applied at the same time. Measurements were made on the auricle photographs using the Photoshop software, and these were analyzed alongside the results of the personality test. Ear length, ear angle, helix thickness, intertragic notch length, anatomy of the lobule of auricle, tragus-antihelix distance, and helix-antihelix distance all give us information on our personality characteristics. The auricle is a defining feature of the face. Besides, being important in medical branches with its unique structure, the anatomy of the auricle has also gained importance by giving us clues on our personality characteristics.